(untitled) (Homoeopathy for All, 2025)
Medicinal plants have been found useful in the cure of a number of diseases including bacterial diseases. Nimba is a very useful medicinal plant in the sub-continent and each part of the plant has medicinal properties. Almost every part of the plant has been in use since ancient times to treat a number of human ailments and also as a household pesticide. The extract from bark, leaves, fruits and root have been used to control leprosy, intestinal helminthiasis and respiratory disorders in children. Flavonoids, flavono glycosides, dihydrochalcones, tannins and others are also important constituents of bark, leaves, fruits and flowers of Nimba. Present study aimed at development and establishment of the HPTLC fingerprint profile and phytochemical screening of Nimba leaf and stem bark.